TURNAROUND TIME UJI COCOK SERASI DI PELAYANAN BANK DARAH (Turnaround Time Cross Match in the Blood Bank) - Glent Nurtanio; Rachmawati Muhiddin; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Turnaround Time (TAT) is the time between the blood request form arriving at the blood bank and when it is issued by the bloodbank. Blood Bank RSWS standard on the TAT of Stat blood service is <45 minutes and is regularly <60 minutes. The aim of this researchwas to know the TAT of blood services at the Blood Bank of the Dr Wahidin Sudirohusodo Hospital, Makassar. The research was carriedout by cross sectional study between August until November 2013. The data were divided into two (2) categories, which were Stat andregular blood service. The blood service was divided into three (3) service times, morning (08:00–14:00), afternoon (14:00–21:00) andevening (21:00–08:00). The statistical method used was Independent Samples T Test. There were 1.366 blood services consisting of 831Stat blood service with average TAT about 37.15 minutes (82.9% complied to standard) and 535 regular blood service with averageTAT about 45.73 minutes (96.1% complied to standard). There were significant differences between morning and afternoon (p=0.000)and between afternoon and evening Stat TAT (p=0.003), but there was no significant difference between morning and evening StatTAT (p=0.196). No significant difference was found in regular TAT between the morning and afternoon session (p=0.915), as well asnoon and evening (p=0.490); and morning and evening session (p=0.428). The TAT blood service at the Dr. Wahidin SudirohusodoHospital Blood Bank which was carried out by gel method should shorten the waiting time of Stat and regular blood service, but not upto 100% yet. Based on this study, the researchers recommended to do some regulation changes in the blood service system especiallyfor the morning and evening Stat sessions.